Control of Staphylococcal-mediated endogenous protease activity alters wound closure time in a complex wound model. Issue 2 (February 2022) - Issa, Rahaf; Thompson, Kate L.; Price, Bianca L.
Highlights: Staphylococcal products elevate protease activity in a 3D wound model. Staphylococcal-mediated proteases delay the proliferative phase of wound healing. ORC/collagen dressing reverses protease levels in inflamed wound model to offset. Dressing application accelerates the rate of wound healing. Abstract: Background: Elevated protease activity is a characteristic feature of chronic wounds, where the inflammatory phase of wound healing is prolonged. The choice of dressings in treatment of chronic wounds can change the nature of the wound base and have a significant impact on healing. Objective: To evaluate the impact of oxidised regenerated cellulose/collagen dressings on Staphylococcal-mediated protease activity in an inflamed wound model. Methods: We developed an in vitro 3D inflamed wound model, and simulated inflammation by exposing the models to Staphylococcal spent culture supernatant. Protease activity and wound healing were assessed in the presence/absence of the dressings. Results: Histological analysis of the wound model revealed two distinct layers, an epidermal and dermal layer, similar to the organisation of human skin. Inflammation with Staphylococcal spent culture supernatant elevated protease levels by 1.7x and consequently prevented the wound from progressing to the proliferative phase of healing, without having a negative effect on cell viability. Adding a collagen dressing, known to have non-specific protease modulating properties, reduced Staphylococcal-mediated protease activity back to baseline, with a concomitant reduction in wound closure time. Inflamed wounds thus resembled unwounded skin after 10 days of treatment with the dressings. Conclusion: Our findings support the further evaluation and use of oxidised regenerated cellulose/collagen dressings for inflamed, non-healing wounds in the clinical setting. The model used in this study has the potential to be applied in preclinical research; to test wound dressing performance, such as healing and cell viability, and to also assess key markers of inflammation.